FinEduPlay: revolutionizing financial education for young minds through gamified learning / Geetha Muthusamy ... [et al.] - Muthusamy, Geetha; Mohd Jaffri, Nursyafiqah; Mohd Hasni, Nur Hanis Farhana; A D Osmara, Nur Nabilah (Universiti Teknologi MARA, Kedah, 2023)
Fostering early education in saving money is a great foundation for future financial success. FinEduPlay is a mobile application that makes learning about financial literacy fun and engaging for school children through gamification. The app offers engaging and fun activities that help children learn valuable skills in money management. This innovative approach has the potential to improve children's financial decision-making skills and increase their financial literacy. The novelty feature of the app motivates children to save money by offering incentives for achieving various milestones during a specific period. The challenge will include interactive features like a virtual piggy bank that will help you track your progress toward your savings goal. The quiz game related to financial literacy in the apps has a system of leveling that makes them excited to level up and gain knowledge as well. Users also can choose their favorite animal as their character of the money box such as a cat, dog, or cow, and name it. Teaching children about financial literacy can be a fun and effective way to give them a head start on making wise financial choices as adults. They can learn valuable skills through games and activities that will help them save money and make smart financial decisions. In Malaysia, the potential for this app is immense, given the opportunity to improve financial literacy among its population despite the challenges in accessing financial education. The study conducted by the Employees Provident Fund (EPF) in 2020 shows that there is room for improvement in financial literacy among Malaysians. While only 35% demonstrated adequate knowledge of financial matters, there is potential for more people to gain these skills. If financial literacy is coordinated in all schools in Malaysia, the potential for the commercialization of this application is high.